Dental Pulp Stem Cells (DPSCs): An Overview - Kalpna Thakur; Rubeena Anjum; Rajesh Thakur; Nitish Bhat; Akanksha Dhiman; Deepti Garg (Journal of Medical Biomedical and Applied Sciences, 2021)
Dental pulp stem cells (DPSCs) are a promising source of cells for numerous and varied regenerative medicine applications. Their natural function in the production of odontoblasts to create reparative dentin support applications in dentistry in the regeneration of tooth structures. Numerous studies have provided evidence of DPSCs’ differentiation capacity, such as in neurogenesis, adipogenesis, osteogenesis, chondrogenesis, angiogenesis, and dentinogenesis. The molecular mechanisms and functions of DPSCs’ differentiation process are affected by growth factors and scaffolds. For example, growth factors such as basic fibroblast growth factor (bFGF), transforming growth factor-β (TGF-β), nerve growth factor (NGF), platelet-derived growth factor (PDGF), and bone morphogenic proteins (BMPs) influence DPSC fate, including in differentiation, cell proliferation, and wound healing. It is clear that a deep understanding of the mechanisms of stem cells, including their aging, self-renewal, microenvironmental homeostasis, and differentiation correlated with cell activity, the energy for which is provided from mitochondria, should provide new approaches for DPSC research and therapeutics.